Geographic Information System-Based Analysis of Flood-Affected Infrastructure in Kembangan Sub-District - Varecha, Prima Vitra; Daryono, Daryono; Triutomo, Sugeng; Tresnanti, Desratri Timur; Widodo, Pujo; Kusuma, Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2024)
Flood is one of the hydrometeorological disasters that have occurred in Indonesia in recent years. Jakarta is one of the cities that is prone to flood. This research was conducted to analyse the infrastructure affected by floods in Kembangan Sub-district, West Jakarta based on Geographic Information System. Data processing was processed using QGIS 3.16, and then analysed using Excel. The results show that Kembangan Sub-district has low physical vulnerability. However, physical vulnerability can increase if more infrastructure is affected if flooding is not taken seriously by the community and government.